Caffeine-Boosted Cryopreservation: Improving Post-Thaw Motility and Kinetics of Red Junglefowl Sperm - Md. Kamruzzaman; Miah, Abdul Gaffar; Mehta, Basant Kumar; Mobarak, Md. Hosne; Salma, Ummay (International Journal of Applied Sciences and Biotechnology, 2026)
This study investigated the improvement of post-thaw motility and kinetics of Red Junglefowl sperm cryopreserved using extender supplemented with caffeine as an effective cryoprotectant. Semen samples collected from the cocks were cryopreserved using extenders containing 8% dimethyl sulfoxide and varying concentrations of caffeine (0, 1, 2, and 3 mg/ml) assigned into 4 treatment groups: T0, T1, T2, and T3, respectively. Post-thaw sperm motility and kinetic parameters were evaluated. The results demonstrated that the supplementation of 2 mg/ml caffeine (T2 group) significantly (P<0.05) enhanced post-thaw motility, progressive motility, and velocity compared to other treatment groups (T0, T1 and T3). The highest values for curvilinear velocity, average path velocity, and straight-line velocity were observed in sperm treated with 2 mg/ml caffeine, suggesting its role in mitigating cryodamage and improving sperm quality. Furthermore, straightness, linearity, and wobble indices were significantly (P<0.05) improved in the T2 group compared to other treatment groups. The amplitude of lateral head displacement and beat cross frequency were also influenced by caffeine supplementation recorded in T2 group. These findings indicated that caffeine served as an effective cryoprotective additive in avian semen cryopreservation. The supplementation of caffeine, particularly at 2 mg/ml, enhanced post-thaw sperm motility and kinetic properties, making it a promising candidate for improving the effectiveness of semen preservation protocols. Further studies are required to assess its impact on fertilization success rates in artificial insemination and long-term genetic conservation programs. This protocol could revolutionize avian genetic resource banking, particularly for threatened species like Red Junglefowl. Int. J. Appl. Sci. Biotechnol. Vol 14(1): 14-21.